A Dynamic Investigation of a Solar Absorption Plant with Nanofluids for Air-Conditioning of an Office Building in a Mild Climate Zone - Luca Cirillo; Sabrina Gargiulo; Adriana Greco; Claudia Masselli; Sergio Nardini; Vincenzo Orabona; Lucrezia Verneau (Energies)
This study explores the impact of using water-Al2O3 nanofluids, at different nanoparticle concentrations, in solar thermal collectors for solar cooling applications. Improving the seasonal energy performance of solar cooling systems is a current research priority, and this work investigates whether nanofluids can significantly enhance system efficiency compared to traditional heat transfer fluids. A transient simulation was carried out using a dynamic model developed in TRNSYS (TRANsient SYstem Simulation), evaluating the system performance throughout the cooling season. The results show that in July, under low volumetric flow conditions and with nanoparticle concentrations of 0.6% and 0.3%, the solar fraction reaches a maximum value of 1. Using a nanofluid at 0.6% concentration leads to significantly higher fractional energy savings compared to pure water. Despite increased pumping energy, the overall energy savings—which include the contribution from an auxiliary boiler—exceed 80% when nanofluids are used. This study goes beyond previous work by providing a dynamic, system-level simulation of nanofluid-enhanced solar cooling performance under realistic operating conditions. The findings demonstrate the practical potential of nanofluids as a valid and more energy-efficient alternative in solar thermal applications.